2003
DOI: 10.1002/eji.200324074
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage colony‐stimulating factor‐dependent macrophage proliferation is mediated through a calcineurin‐independent but immunophilin‐dependent mechanism that mediates the activation of external regulated kinases

Abstract: Calcineurin is constitutively expressed in bone marrow-derived macrophages. However, macrophage response to macrophage colony-stimulating factor (M-CSF) was not impaired by the use of either calcineurin inhibitors (W-13, chlorpromazine and trifluoperazine), calcium chelators (BAPTA-AM) or Ca 2+ channel antagonists (verapamil, nifedipine and diltiazem). Inhibition of calcineurin expression by inhibitory antisense RNA treatment did not result in an inhibition of M-CSF-dependent proliferation. Only very high dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…This correlates with the induction of MKP-1 [15,16]. Moreover, conditions that block MKP-1 induction by M-CSF elongate ERK activity and inhibit proliferation [10,11]. This observation is supported by the finding that mice lacking MKP-1 have enhanced MAPK activity [48].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This correlates with the induction of MKP-1 [15,16]. Moreover, conditions that block MKP-1 induction by M-CSF elongate ERK activity and inhibit proliferation [10,11]. This observation is supported by the finding that mice lacking MKP-1 have enhanced MAPK activity [48].…”
Section: Discussionmentioning
confidence: 84%
“…For proliferation, ERK must be dephosphorylated approximately 15 min after activation [9]. A number of conditions that elongate ERK activity, for example extracellular matrix proteins, such as decorin or fibrinogen, or treatment with cyclosporin A or FK506 reduce proliferation [10,11]. Recently, we have shown that inhibition of MAP kinase phosphotose-1 (MKP-1) expression using siRNA leads to elongated ERK phosphorylation and blockage of M-CSF-dependent proliferation [12].…”
mentioning
confidence: 99%
“…Our experiments show that genes regulated through these pathways are not affected by the inhibition of deacetylase activity. The activation of ERK1/2 is required for GM-CSF-and M-CSF-dependent macrophage proliferation (33,34). However, TSA did not affect M-CSF-dependent proliferation, which implies that genes that require the ERK pathway are not inhibited.…”
Section: Discussionmentioning
confidence: 98%
“…This observation also demonstrates that TSA, at the concentration used in our assays, did not induce cellular toxicity. Stimulation of macrophage proliferation by both M-CSF and GM-CSF requires the activation of extracellular signal-regulated kinases or ERKs (33,34). The observation that TSA did not affect M-CSFinduced proliferation indicates that this inhibitor/drug does not target ERKs.…”
Section: Deacetylase Activity Is Required For Gm-csf-dependent Prolifmentioning
confidence: 99%
“…Cyp-A was originally discovered as an intracellular ligand for cyclosporin A, an immunosuppressant (Handschumacher et al, 1984), but other functions have also been suggested. The secreted form of Cyp-A is a potent chemoattractant for macrophage colony-stimulating factor (MCSF)-dependant macrophages (Comalada et al, 2003;Sà nchez-Tilló et al, 2006), monocytes (Galat, 1993;Payeli et al, 2008), neutrophils (Sherry et al, 1992), eosinophils (Xu et al, 1992), and T cells (Kasinrerk, 1999). This molecule is involved in the adhesion of monocytes/macrophages to the extracellular matrix (Yang et al, 2008) and the migration of murine bone marrow cells (Khromykh et al, 2007).…”
Section: Discussionmentioning
confidence: 99%